PENGARUH LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Husna, Husna; Sahade, Sahade; Afiah, Nur. (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study is to ascertain how leverage affects accounting conservatism in manufacturing firms in the consumer products sector that are listed on the Indonesia Stock Exchange. The factors in this study are accounting conservatism and leverage. The sample in this study consists of manufacturing companies whose consumer goods industry sector is listed on the Indonesia Stock Exchange during the 2019–2020 period. These companies publish financial reports separately. The population in this study consists of all manufacturing companies in the consumer goods industry sector that are listed on the Indonesia Stock Exchange. Those businesses in the consumer goods industry sector that have non-negative profit values, which were selected using a purposive sample approach, will be listed on the Indonesian Stock Exchange website during the 2019–2020 period. Data analysis and documentation approaches were used in the data collecting process. The findings of this study show that although there are still a number of companies that have suffered a decline due to an increase in total corporate debt, the average leverage, as determined by the debt to equity ratio, has increased in Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange. A straightforward linear regression analysis reveals that the constant value is 36,174. Hence, the accounting conservatism in Manufacturing Firms in the Consumer Goods Industry Sector Listed on the Indonesian Stock Exchange is 36,174 if the leverage value is zero. The regression coefficient result is 0.386, which indicates that the accounting conservatism in Manufacturing Firms in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange is 0.386 if the leverage variable increases by 1%.Keywords: Leverage and Accounting Conservatism